Assessing Innovative Activity and Commercialization in SMEs – A Study of SMEs in Punjab - Rehman, Munib ur; Rehman, Syed Khalil ur; Khan, Romaisa (Devotion : Journal of Research and Community Service, 2023)
Small and medium Enterprises are vital in the economy of any country. They generate employment, business besides supporting big industries. Improvement in the services and products of SMEs ensures their survival and transformation to the bigger institutions, In Pakistan Majority of enterprises are SMEs and are pivotal in strengthening the national economy. How they are improving their working at par with market needs is the subject touched upon very little in Pakistani environment. This study aims at mapping the innovation practices in the SMEs irrespective their sector in terms of commercialization so as to ascertain their strategies for better service and production delivery which is significant in their survival. For the purpose. 250 SMEs, selected through purposive random sampling with the help of SMEDA, Provincial Industries Departments, SECP and Lahore Chamber of Commerce and Industry, around the country were studied. Data was collected through an online questionnaire, based on the work Tim Mazzarol et al (2011), comprising 40 items. 12 respondents were interviewed through semi-structured interviews. This study is of articulation in nature and data was analyzed SPSS and Envivo. The results indicated the patterns and preferences of SMEs towards innovation and commercialization by giving a bleak picture in SMEs. The findings suggest massive change of policies in SMEs to make them real booster of economy.